Hematological profile, inflammatory markers and serum liver enzymes in COVID 19 positive children vs. COVID 19 negative ones—a comparative study - Pavelescu, Mirela Luminița; Dinulescu, Alexandru; Păsărică, Alexandru-Sorin; Dijmărescu, Irina; Păcurar, Daniela (Frontiers in Pediatrics, 2024)
1) Background: Complete blood count, C-reactive protein and transaminases are routine laboratory parameters investigated in children with infections, including COVID 19. We aimed to evaluate the diagnostic accuracy of these parameters in children diagnosed with COVID 19. (2) Methods: At the time of admission, children with COVID 19 suggestive symptoms were tested RT-PCR for SARS CoV-2 and were allocated to either the study group (RT-PCR SARS CoV-2 positive) or control group (RT-PCR SARS CoV-2 negative). All children were evaluated by complete blood count, CRP, and transaminases. (3) Results: When comparing the two groups, we identified significantly lower values for leukocytes (p<0.001), neutrophils (p<0.001), lymphocytes (p<0.001) and thrombocytes (p=0.014), but no significantly different values for CRP (p=0.916) and monocytes (p=0.082). A diagnostic score for COVID-19 was compiled using the abovementioned parameters -presence of fever, number of lymphocytes and aspartate-aminotransferase. Performance was tested, showing a positive discrimination value (AUC of 0.703) -81.5% sensitivity, 50.6% specificity. (4) Conclusions: The leukocytes, neutrophils and lymphocytes have significantly lower values in COVID-19 children. The proposed score based on the presence of fever the values of lymphocytes and AST has a good sensitivity in predicting COVID-19 infection.